The impact of a speaker’s voice quality on auditory perception and cognition: a behavioral and subjective approach - Schiller, Isabel S.; Aspöck, Lukas; Schlittmeier, Sabine J. (Frontiers in Psychology, 2023)
Our voice is key for conveying information and knowledge to others during verbal communication. However, those who heavily depend on their voice, such as teachers and university professors, often develop voice problems, signaled by hoarseness. The aim of this study was to investigate the effect of hoarseness on listeners' memory for auditory-verbal information, listening effort, and listening impression. Forty-eight normally-hearing adults performed two memory tasks that were auditorily presented in varied voice quality (typical vs. hoarse). The tasks were Heard Text Recall, as part of a dual-task paradigm, and auditory Verbal Serial Recall (aVSR). Participants also completed a listening impression questionnaire for both voice qualities. Behavioral measures of memory for auditory-verbal information and listening effort were performance and response time. Subjective measures of listening effort and other aspects of listening impression were questionnaire rating scores. Results showed that, except for the aVSR, behavioral outcomes did not vary with the speaker's voice quality. Regarding the aVSR, we found a significant interaction between voice quality and trial, indicating that participants' recall performance dropped in the beginning of the task in the hoarse-voice condition but not in the typical-voice condition, and then increased again toward the end. Results from the listening impression questionnaire showed that listening to the hoarse voice resulted in significantly increased perceived listening effort, greater annoyance and poorer selfreported performance. These findings suggest that hoarseness can, at least subjectively, compromise effective listening. Vocal health may be particularly important in the educational context, where listening and learning are closely linked.